Prospective evaluation of venous access difficulty and a near‐infrared vein visualizer at four French haemophilia treatment centres. (21st October 2014) - Guillon, P.; Makhloufi, M.; Baillie, S.; Roucoulet, C.; Dolimier, E.; Masquelier, A.‐M.
Summary Although a serious impediment in haemo‐philia patients, difficulty accessing peripheral veins has received little attention in clinical studies. New peripheral vein visualization devices could potentially ameliorate difficult venous access (DVA), but their utility remains unproved. The study aim was to survey the frequency, causes and clinical manifestations of DVA and evaluate the clinical utility of a near‐infrared (NIR) vein visualizer. In this multicentre prospective study, methods, difficulties and outcomes of venous access were assessed for a single venipuncture in consecutive patients. The impact of an NIR vein visualizer on vein localization, the number of venipuncture attempts and patient stress and pain was determined. Among 450 total patients enrolled, venous access was judged to be difficult in 165 (36.7%), most often because of poor vein condition, young patient age, overweight and difficulty in finding veins. Of the patients with DVA, difficulty in locating veins was encountered in 82.4%, and more than one venipuncture attempt was required in 24.8%. Veins were difficult to locate in significantly fewer DVA patients (P = 0.002) when the NIR vein visualizer was used (76.0%) than not used (92.3%). Pain during venipuncture in DVA patients was also significantly less common (P = 0.019) with use of the NIR vein visualizer (34.0% vs. 55.4%). No effect was observed on venipuncture attempts. DVA affects more than one‐third of patients at haemophilia treatment centres. An NIR vein visualizer showed significant promise for facilitating vein location and mitigating patient pain in those patients.